Imunoterapia anti-tumoral com células dendríticas - Oliveira, T.G (2013)
Dendritic cells (DCs) are professional antigen-presenting cells, which display an extraordinary capacity to induce and regulate T-cell responses. Because of their immunoregulatory capacities and because very small numbers of activated DCs are highly efficient in generating immune responses against antigens, DCs have been extensively used in clinical trials in order to elicit or amplify immune responses against cancer. While clinical trials provide evidence that dendritic cells vaccines are safe and elicit immunological responses in most patients, few complete tumor remissions have been reported. To improve the clinical efficacy, it is mandatory to design novel and improved strategies that can boost adaptive immunity to cancer helping to overcome regulatory T cells and allowing the breakdown of the immunosuppressive tumor microenvironment. The association of DCs vaccines with conventional chemo- and radiotherapy protocols could enhance DCs activation and antigen cross-presentation, selectively eliminating immunosuppressive cells, thus reverting the immunosuppression state caused by cancer, suggesting that relevant chemoimmunotherapy associa- tions could fully exploit DC capacity to trigger anticancer responses.